2016
DOI: 10.4193/rhino15.284
|View full text |Cite
|
Sign up to set email alerts
|

Using postoperative SNOT-22 to help predict the probability of revision sinus surgery

Abstract: Background: There is a need to develop a patient-level strategy to identify those at higher risk of requiring revision ESS since this may assist clinicians in tailoring their postoperative management. This study evaluated whether identifying changes in the post- operative 22-item Sinonasal Outcome Test (SNOT-22) can help identify patients at increased risk of needing revision sinus surgery for refractory chronic rhinosinusitis (CRS). Methods: 668 CRS patients undergoing primary ESS with complete 60-month foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Several clinical markers raising the risk of recurrence have been reported: tissue eosinophilia, 3 , 23 25 serum eosinophilia, 3 high computed tomography (CT) scores, 1 , 3 , 26 higher preoperative endoscopic Lund-Kennedy scores for polyposis, 27 radiological inflammatory findings in frontal sinuses 17 and changes in SNOT-22 scoring after surgery. 28 …”
Section: Introductionmentioning
confidence: 99%
“…Several clinical markers raising the risk of recurrence have been reported: tissue eosinophilia, 3 , 23 25 serum eosinophilia, 3 high computed tomography (CT) scores, 1 , 3 , 26 higher preoperative endoscopic Lund-Kennedy scores for polyposis, 27 radiological inflammatory findings in frontal sinuses 17 and changes in SNOT-22 scoring after surgery. 28 …”
Section: Introductionmentioning
confidence: 99%
“…After informed consent was obtained each participant completed a copy of the Sino-Nasal Outcome Test-22 (SNOT-22), Nasal Obstruction Symptom Evaluation (NOSE) and 36-Item Short Form Survey (SF-36). The SNOT-22 is a questionnaire consisting of 22 questions evaluating a range of symptoms experienced by suffers of nasal disease (24). The NOSE questionnaire consists of five questions which predominantly focus on evaluating breathing difficulties (25).…”
Section: Methodsmentioning
confidence: 99%
“…as Cox's proportional hazard models [13,15,16] or logistic regression models [14,15,18,20]. Such studies have assumed associations are linear and that an alpha error <5% indicates the importance of a predictor.…”
Section: Plos Onementioning
confidence: 99%
“…Revision ESS risk was previously studied at the population level using Cox's proportional hazard [13,15,16] or logistic regression [14,15,18,20] models, which usually assume associations are linear and that an alpha error <5% indicates the importance of a predictor. Using these assumptions, previous studies have demonstrated that a younger age associated with revision ESS [13,66].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation